(untitled) (International Journal of Natural Sciences, 2016)
Retention of fetal membrane (RFM) in dairy cows is a common complication after parturition due to failure of the separation of villi of fetal cotyledon from crypts of maternal caruncles and affects on reproductive cycle. The present study was conducted in 594 cows of 15 different dairy farms of Sylhet district. The data was collected by direct interviewing of the farmers in a prescribed questionnaires data sheet and data record from the register of the contracted farms. The overall incidence of retained placenta was 17.51 %.The cross bred dairy cows had higher incidence (14.14%) of RFM compared to local one (3.04%) and differ significantly (p <0 .05). The parity and age of the animals had substantial effect on retention of fetal membrane in dairy cows. The incidence of RFM had notably increased from 1st parity (10.04 %) to 7th parity (57.14 %) and the highest observation was found at more than 7 years and lowest at the age below 3 years of age. The season, sex of calves, body condition of the animals and level of vitamin AD3E before parturition had significant effect on incidence of RFM in dairy cows. The RFM affected cows were treated either with intra muscular injection of oxytocin or herbal drug Eutoklin and manually removing the retained membrane. RFM affected post partum first estrus, service per conception, days open and calving interval significantly on parturated cows compared to normal delivered cows. Younger healthy cows, supply of balanced diet, sufficient daily exercise; comfortable calving areas should be maintained to reduce the incidence of RFM. International Journal of Natural Sciences (2015), 5(2) 93-97